Rethinking the Qur’an’s Literary Evolution: Nicolai Sinai’s Approach to Inner-Qur’anic Chronology - Amini, Hanifah; Randy Putra Alamsyah; Dedi Masri; Mariam Ahmed Zanan Alzahrani (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2024)
The article critically examines Nicolai Sinai’s conception of inner-Qur’anic chronology and its implications for understanding the Qur’an’s literary evolution. His approach represents a methodological continuation and refinement of the 19th-century chronological models developed by Nöldeke, yet it departs from them through a more rigorous empirical and literary-philological analysis. By employing three key parameters, namely verse length, mean verse length, and structural complexity, Sinai reconstructs the Qur’an’s gradual compositional development and argues that the stylistic variation corresponds to successive stages of revelation. This article further examines the thematic and rhetorical progression across the Meccan and Medinan periods, highlighting how shifts in literary form parallel the transformation of the Prophet Muhammad’s role from an eschatological warner to the leader of religious and social community. It argues that Sinai’s framework provides a coherent model for understanding the Qur’an as a dynamically developing text rather than a static corpus. The article contributes to Qur’anic studies by positioning literary evolution as a central analytical category that links stylistic analysis, diachronic interpretation, and historical reconstruction.